2020
DOI: 10.1021/acs.macromol.9b02645
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Injection of Polymer into a Spherical Cavity from a Narrow Tube

Abstract: The spontaneous injection of a polymer chain into a spherical cavity from a narrow cylindrical tube is investigated by using Monte Carlo simulation. A continuous phase transition from a partially injected state to a completely injected state is found at the critical radius (R C ) of the spherical cavity. The dependence of R C on the polymer length (N) and the radius of tube (r) can be described by a scaling relation R C ∝ N 1/3 r 1−1/3ν with ν as the Flory exponent. In the partially injected phase, the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is worth noting that the difference between the flat plate and the channel cases is significant and complicated. Namely, according to the literature, there is no restriction when the polymer chains come to the surface of the plate, but for the cylindrical channel, the polymer chains are supposed to naturally escape due to the entropy loss when the chain size is on the order of magnitude of channel size. Such an escape effect in the cylindrical channel needs to be further clarified in the future by theoretical consideration and computational simulation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is worth noting that the difference between the flat plate and the channel cases is significant and complicated. Namely, according to the literature, there is no restriction when the polymer chains come to the surface of the plate, but for the cylindrical channel, the polymer chains are supposed to naturally escape due to the entropy loss when the chain size is on the order of magnitude of channel size. Such an escape effect in the cylindrical channel needs to be further clarified in the future by theoretical consideration and computational simulation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure 2 shows the dependence of the complete injection probability P in on the radius of the sphere R for different polymer lengths N at f = 0.5. We can see two polymer states: a partial injection state with P in roughly zero at small R and a complete injection state with P in roughly 1 at large R. There is an obvious sharp transition from the partial injection state to the complete injection state at a special R. To give approximately the radius of the spherical cavity where the transition occurs, we here define the transition radius R C at which P in = 0.5, [59] as shown in Fig. 2, and the corresponding effective transition radius is R eC = R C − 0.56.…”
Section: Complete Injection Probability and Transition Radius Of The ...mentioning
confidence: 99%
“…In our recent work, we have studied the spontaneous injection of a flexible polymer into a spherical cavity from a long channel. [59] It was found that there is an obvious transition for polymer from the partial injection to the complete injection with increasing the radius of the cavity. However, the transition is not clear yet for forced cases.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor that affects the translocation or ejection dynamics is the geometry of the trans side, i.e. the available space for the polymer in the trans side, which can be semispace [3,, confined in one dimension [33][34][35], or confined in two and three dimensions [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The latter case corresponds to the packing/ejection of a DNA or RNA of a virus into/from a capsid.…”
Section: Introductionmentioning
confidence: 99%